Developing a open-source serious game for control and education on HPV and Cervical Cancer - Pereira, Igor Muzetti; Lelis, Vinícius Victor (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2019: Anais do XVI Congresso Latino-Americano de Software Livre e Tecnologias Abertas, 2019)
HPV - short for human papillomavirus - is a virus capable of infecting the mucous membranes and skin, being the most prevalent involved on Sexually Transmitted Diseases and the main cause of Cervical Cancer. However, reaching out to and inviting all eligible people for cervical cancer screening and vaccination against HPV is a difficult task. A possible solution is the use of social inducement and gamification through modern means of communication, which may encourage the attendance of unscreened or unvaccinated people on related programs. Therefore, this paper presents the development of a serious game for the Android platform designed for children and preteens with the purpose of foresting HPV and Cervical Cancer awareness, informationseeking, and communication, thus possibly increasing the number of vaccinated and screened people.